Gender differences in the concentration of individual performance: evidence from track and field athletics - Frick, B. (Journal of Sports Economics, 2025)
Until recently, the under-representation of women in top management and government positions has been attributed to discriminatory hiring and promotion policies. A rather new perhaps competing explanation is that women tend to avoid competitive settings due to mental dispositions and personality traits that are different from those of men. In this article, the performance of female and male elite athletes in one of the traditional Olympic sports, track and field athletics, is analyzed over an extended period (2001-2021). Since elite athletes have self-selected into a highly competitive environment, significant differences between the genders in terms of their observable collective behavior, that is the homogeneity of the individual performances, are highly unlikely. The empirical analyses show that the gender gap in competitive intensity, that is the dispersion in elite performances, is already quite small and will have completely disappeared in a few years.